2015
DOI: 10.3389/fpsyg.2015.01573
|View full text |Cite
|
Sign up to set email alerts
|

Contingent self-esteem and vulnerability to depression: academic contingent self-esteem predicts depressive symptoms in students

Abstract: Low self-esteem has been established as a vulnerability factor for depression. In line with recent research, we suggest that a full understanding of the role of self-esteem in depression requires consideration of contingent self-esteem as well. For most people, competence is an important source of self-esteem. Students in particular link their self-esteem to academic competence. To test the hypothesis that academic contingent self-esteem (aCSE) predicts depressive symptoms (DS), two studies were conducted. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 62 publications
3
34
0
1
Order By: Relevance
“…The presence of AUD or drinking in general at an early age may lead to environmental stressors (i.e. poor academic performance, poor relationship with parents, legal problems) 6466 , which in turn may lead to MDD. Moreover, AUD and drinking may lead to biological changes that may lead to increased vulnerability to MDD 67 .…”
Section: Resultsmentioning
confidence: 99%
“…The presence of AUD or drinking in general at an early age may lead to environmental stressors (i.e. poor academic performance, poor relationship with parents, legal problems) 6466 , which in turn may lead to MDD. Moreover, AUD and drinking may lead to biological changes that may lead to increased vulnerability to MDD 67 .…”
Section: Resultsmentioning
confidence: 99%
“…The secure form of self-esteem is based on acceptance of self-traits and heightened awareness. This is not based on self-evaluative methods and social comparison (Schöne et al, 2015;Woods et al, 2006). Thus, this secure selfesteem based on acceptance of self-traits and heightened awareness may lead to stable resilience and quicker return to a state of equilibrium in the presence of stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, prior studies could not find age‐specific differences for adolescents in different phases of puberty. In contrast, research has shown that depressive symptoms typically increase with the onset and during puberty (Schöne, Tandler, & Stiensmeier‐Pelster, ). Therefore, another aim of the present study is to explore whether relations of interest vary in strength for different phases of puberty.…”
Section: Introductionmentioning
confidence: 95%
“…Although little is known about the role of PACPR and PACNR in this context, empirical evidence consistently demonstrated associations between psychological control and depressive symptoms (Barber, ; Pinquart, ; Soenens, Luyckx, Vansteenkiste, Duriez, & Goossens, ). Moreover, research has shown associations of academic CSE with depressive symptoms in university students (Schöne et al, ) and adolescents (Burwell & Shirk, ). A recent study additionally provided direct evidence for the mediating role of CSE in associations between parental conditional regard and adolescents’ depressive symptoms (Wouters et al, ).…”
Section: Introductionmentioning
confidence: 99%